Transient convection finite difference solution - Agapin, Dennis Rio
Most commonly encountered studies of convection do not deal with time-variable conditions, but rather permanent conditions i.e. stationary velocity and temperature fields. This is probably due to calculation difficulties in terms of time and cost of computation. Transient conversion deals with time-variable boundary layer equations. In this study, we will investigate transient convection in a horizontal rectangular enclosure where one wall is at a high temperature, the other wall is at a low temperature and the other two walls are adiabatic.